Integrating network pharmacology and experimental verification to decipher the multitarget pharmacological mechanism of Cinnamomum zeylanicum essential oil in treating inflammation - Debajani Mohanty; Sucheesmita Padhee; Chiranjibi Sahoo; Sudipta Jena; Ambika Sahoo; Pratap Chandra Panda; Sanghamitra Nayak; Asit Ray (Heliyon, 2024)
Inflammatory diseases contribute to more than 50 % of global deaths. Research suggests that network pharmacology can reveal the biological mechanisms underlying inflammatory diseases and drug effects at the molecular level. The aim of the study was to clarify the biological mechanism of Cinnamomum zeylanicum essential oil (CZEO) and predict molecular targets of CZEO against inflammation by employing network pharmacology and in vitro assays. First, the genes related to inflammation were identified from the Genecards and Online Mendelian Inheritance in Man (OMIM) databases. The CZEO targets were obtained from the SwissTargetPrediction and Similarity Ensemble Approach (SEA) database. A total of 1057 CZEO and 526 anti-inflammation targets were obtained. The core hub target of CZEO anti-inflammatory was obtained using the protein–protein interaction network. KEGG pathway analysis suggested CZEO to exert anti-inflammatory effect mainly through Tumor necrosis factor, Toll-like receptor and IL-17 signalling pathway. Molecular docking of active ingredients-core targets interactions was modelled using Pyrx software. Docking and simulation studies revealed benzyl benzoate to exhibit good binding affinity towards IL8 protein. MTT assay revealed CZEO to have non-cytotoxic effect on RAW 264.7 cells. CZEO also inhibited the production of NO, PGE2, IL-6, IL-1β and TNF-α and promoted the activity of endogenous antioxidant enzymes in LPS-stimulated RAW 264.7 cells. Additionally, CZEO inhibited intracellular ROS generation, NF-kB nuclear translocation and modulated the expression of downstream genes involved in Toll-like receptor signalling pathway. The results deciphered the mechanism of CZEO in treating inflammation and provided a theoretical basis for its clinical application.